2014
DOI: 10.1016/j.bmcl.2014.07.077
|View full text |Cite
|
Sign up to set email alerts
|

‘Click’ assembly of glycoclusters and discovery of a trehalose analogue that retards Aβ40 aggregation and inhibits Aβ40-induced neurotoxicity

Abstract: Abstract:Osmolytes have been proposed as treatments for neurodegenerative proteinopathies including Alzheimer's disease. However, for osmolytes to reach the clinic their efficacy must be improved. In this work, copper(I)-catalyzed azide-alkyne cycloaddition chemistry was used to synthesize glycoclusters bearing six copies of trehalose, lactose, galactose or glucose, with the aim of improving the potency of these osmolytes via multivalency. A trehalose glycocluster was found to be superior to monomeric trehalos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…For the PGlcEAm35 solution, A β aggregation rate is initially reduced (Figure 3C, ○), but saturation occurs at similar intensities within 36 h. This suggests that the A β aggregation rate is influenced by the polymers PDMA, PGalEAm, and PGlcEAm35, but these polymers do not influence the final product of A β aggregation (fibrils). Fung et al 21 reported a decrease of the lag phase of A β 42 aggregation in the presence of glucose and galactose monosaccharides, whereas Rajaram et al 44 reported a concentration dependent increase in lag phase for A β 40 aggregation in the presence of glycoclusters made of six units of either glucose or galactose. We observed a minor decrease in lag phase for A β 42 aggregation in the presence of PDMA, PGalEAm, and PGlcEAm35 (Figure 3A–C).…”
Section: Resultsmentioning
confidence: 99%
“…For the PGlcEAm35 solution, A β aggregation rate is initially reduced (Figure 3C, ○), but saturation occurs at similar intensities within 36 h. This suggests that the A β aggregation rate is influenced by the polymers PDMA, PGalEAm, and PGlcEAm35, but these polymers do not influence the final product of A β aggregation (fibrils). Fung et al 21 reported a decrease of the lag phase of A β 42 aggregation in the presence of glucose and galactose monosaccharides, whereas Rajaram et al 44 reported a concentration dependent increase in lag phase for A β 40 aggregation in the presence of glycoclusters made of six units of either glucose or galactose. We observed a minor decrease in lag phase for A β 42 aggregation in the presence of PDMA, PGalEAm, and PGlcEAm35 (Figure 3A–C).…”
Section: Resultsmentioning
confidence: 99%
“…The method used was based on our published protocol (Rajaram et al, 2014), with the main difference being that Aβ 42 was used instead of Aβ 40 . Briefly, low molecular weight (LMW)…”
Section: Tht Fluorescence Assay Of Aβ 42 Fibrillationmentioning
confidence: 99%
“…The connection between these units was accomplished by O -glycosidic bond or via O -methylene 1,2,3-triazole linker, as shown in Scheme 11 . Sugar derivatives of 44 and 45 were prepared according to published procedures [ 30 , 31 , 32 ]; sugar was used to enhance the bioavailability and solubility of potential drugs.…”
Section: Anticancer Activitymentioning
confidence: 99%